Rancang Bangun Sistem Transfer Liquid Berbasis Arduino Uno Menggunakan Sensor YF-S401 - Alfarizky Ilham, Dimas; Al-Azhari, Abdurrakhman Hamid; Djuniadi, Djuniadi (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
This article discusses the design of a liquid transfer system using a YF-S401 flow sensor and the evaluation of various calibration factors to create a reliable system. The research methods included water flow measurement, system component selection, system design, and workflow. The research results showed that a calibration factor of 50 was the optimal choice, showing good liquid transfer precision at a scale of 100 ml. However, testing at a scale of 200 ml and 300 ml showed suboptimal performance, especially in maintaining liquid transfer precision. Further development recommended in the selection of more reliable components, the improvement of the Arduino Uno program, and the implementation of technologies such as real time operating system (RTOS) to improve the accuracy of the liquid transfer system at larger scales. Overall, this research provides important insights for the development of automatic liquid transfer systems with a focus on precision in various measurement scales. Keywords—Liquid transfer system, Flow sensor, Calibration factor, Water flow measurement, Arduino Uno